Lack of short-chain fatty acids and overgrowth of opportunistic pathogens define dysbiosis of neuromyelitis optica spectrum disorders: A Chinese pilot study. (August 2019) - Gong, Junli; Qiu, Wei; Zeng, Qin; Liu, Xiyuan; Sun, Xiaobo; Li, Huijuan; Yang, Yu; Wu, Aimin; Bao, Jian; Wang, Yuge; Shu, Yaqing; Hu, Xueqiang; et al.
Background: Intestinal microbiota is an important environmental factor in the initiation and progression of autoimmune diseases. However, investigations on the gut microbiome in neuromyelitis optica spectrum disorders (NMOSD) are relatively insufficient, especially for that of the Asia population. Objectives: To evaluate whether or not the intestinal microbiota of NMOSD patients had specific microbial signatures. Methods: Next-generation sequencing and gas chromatography were employed to compare the fecal microbial composition and short-chain fatty acids (SCFAs) spectrum between patients with NMOSD ( n = 84) and healthy controls ( n = 54). Results: The gut microbial composition of NMOSD distinguished from healthy individuals. Streptococcus, significantly increased in NMOSD, is positively correlated with disease severities ( p < 0.05). The use of immunosuppressants results in a decrease of Streptococcus, suggesting that Streptococcus might play a significant role in the pathogenesis of NMOSD. A striking depletion of fecal SCFAs was observed in NMOSD patients ( p < 0.0001), with acetate and butyrate showing significantly negative correlation with disease severities ( p < 0.05). Conclusion: The fecal organismal structures and SCFAs level of patients with NMOSD were distinctive from healthy individuals. These findings not only could be critical events driving the aberrant immune response responsible for the pathogenesis of these disorders but could also provide suggestions for disease therapy.